Morals in Social and State Life According to Ibn Miskawaih and Imam Mawardi - Dadang Nur Hidayat; Fahrurrozi, Fahrurrozi; Ekawati, Ekawati (Penerbit Hellow Pustaka, 2025)
This study examines the concept of morals in social and state life according to Ibn Miskawayh and Imam al-Mawardi. Through a qualitative descriptive literature review, this study examines the thoughts of these two figures on the importance of morals as the foundation for character formation in individuals, society, and the state. Ibn Miskawayh emphasized the cultivation and education of morals, as well as the balance between reason, passion, and anger. Imam al-Mawardi highlighted the role of morals in building social solidarity, just leadership, and fair law enforcement. Both agree that morals are the primary foundation for a harmonious society and a just government. The relevance of their thinking is crucial for application in facing the moral, social, political, and legal challenges of the modern era.